Supporting energy technology deployment while avoiding unintended technological lock-in: a policy design perspective - Leonore Haelg; Marius Waelchli; Tobias S Schmidt (Environmental Research Letters, 2018)
Technology deployment policies can play a key role in bringing early-stage energy technologies to the market and reducing their cost along their learning curves. Yet deployment policies may drive unintended and premature lock-in of currently leading technologies. Here we develop an empirically calibrated agent-based model to analyse how deployment policy design influences which technologies are selected by investors. We focus on Germany’s solar photovoltaics feed-in tariff policy between 2003 and 2011 and analyse two design features, technology specificity and application specificity. Our results show that both features are highly important in technology selection and that spillover effects between applications exist. Policies that fail to consider these effects can unintendedly lock in or lock out technologies. To avoid this, policymakers can leverage the fact that different technologies are competitive in different applications and, by designing application-specific deployment policies, effectively offer a level playing field for competing technologies.